HEM 2022
DOI: 10.21272/hem.2022.2-04
|View full text |Cite
|
Sign up to set email alerts
|

Data Management in Healthcare Research as a Guarantee of its Quality

Abstract: Today, in times of outbreaks of epidemics such as the Zika virus and COVID-19, health systems around the globe face an urgent need to respond quickly to overcome their spread and prevent the re-infection of humanity. Among the solutions was the World Health Organization’s call for immediate, rapid, and, most importantly, open dissemination of medical research data. Although data sharing benefits science and society, there is a range of ethical, legal, cultural, financial, and technical barriers to the dissemin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…They also cover different subjects -the state, enterprises, and users. Moreover, the security capabilities of modern technologies are being investigated in various spheres of society's life, for example, health care (Pakhnenko and Pudło, 2023;Rekunenko et al, 2022), social services (Rahmanov et al, 2023), public administration (Pakhnenko and Kuan, 2023;Muradov, 2022). A bibliometric analysis of scientific publications devoted to cybersecurity issues in the context of Industry 4.0 was conducted for a more detailed understanding of research directions devoted to cybersecurity (Appendix A, Figure 1).…”
Section: Literature Reviewmentioning
confidence: 99%
“…They also cover different subjects -the state, enterprises, and users. Moreover, the security capabilities of modern technologies are being investigated in various spheres of society's life, for example, health care (Pakhnenko and Pudło, 2023;Rekunenko et al, 2022), social services (Rahmanov et al, 2023), public administration (Pakhnenko and Kuan, 2023;Muradov, 2022). A bibliometric analysis of scientific publications devoted to cybersecurity issues in the context of Industry 4.0 was conducted for a more detailed understanding of research directions devoted to cybersecurity (Appendix A, Figure 1).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Advancements in such areas as electric vehicles, autonomous driving, smart traffic management, and shared mobility platforms have the potential to transform the way for policy modernization. In addition, scholars [21][22][23][24] have shown that penetrating digital services at all levels boosts the extension of government and public service digitalization, which reduces the eco-destructive impact on the environment.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, 8% of all data management research has been conducted in the medical field. Rekunenko et al (2022) found an upward trend in healthcare data management publications, with the largest growth in 2019 and 2020.…”
mentioning
confidence: 99%